The effect of serum on in vitro maturation, in vitro fertilization and steroidogenesis of bovine oocytes co-cultured with granulosa cells. - Mingoti, Gisele Zoccal [UNESP]; Garcia, J. M.; Rosa-e-Silva, A. A. (My University, 1995)
The influence of fetal calf serum alone (FCS) or associated with proestrous (FCS+PCS), estrous (FCS+ECS) or metaestrous (FCS+MCS) cow serum added to the culture medium and of the steroids produced by co-cultured granulosa cells were evaluated in terms of the in vitro maturation (IVM) and fertilization (IVF) of bovine oocytes. Supplementation of the medium with FCS+ECS and FCS+MCS resulted in higher proportions of oocytes that reached metaphase II (96.0% and 93.3%, respectively) and in higher proportions of embryos that reached the four- and eight-cell/morula stages (51.9% and 65.6%, respectively), whereas the supplementation with FCS and FCS+PCS resulted in only 79.2% and 67.5%, respectively, of matured oocytes and 26.7% and 34.3%, respectively, of cleaved embryos. These findings show that the best IVM and IVF were obtained at lower concentrations of estradiol produced by co-cultured granulosa cells (supplementation with FCS+ECS: 10.3 ng/ml and FCS+MCS: 2.1 ng/ml), whereas the worst results in IVM and IVF occurred at higher concentrations of estradiol that were obtained with FCS (33.1 ng/ml) and FCS+PCS (19.9 ng/ml) supplementation. These data suggest an inhibitory effect of estradiol on resumption of oocyte meiosis in vitro.
Keywords: steroid; animal; biosynthesis; cattle; cell culture; culture medium; estrus; female; fertilization in vitro; fetus blood; granulosa cell; growth, development and aging; oocyte; physiology; prenatal development; Animal; Cattle; Cells, Cultured; Culture Media; Embryo and Fetal Development; Estrus; Female; Fertilization in Vitro; Fetal Blood; Granulosa Cells; Oocytes; Steroids; Support, Non-U.S. Gov't